Genetic diversity of Xylella fastidiosa in citrus producing regions in the state of Bahia, Brazil - Casais, Vinicius Oliveira; do Patrocínio, Epaminondas; Oliveira, Saulo Alves Santos de; Schnadelbach, Alessandra Selbach; Barbosa, Cristiane de Jesus; Barbosa, Luciana Veiga (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate, by SSR markers, the genetic diversity of Xylella fastidiosa in the state of Bahia, Brazil. Two of the main citrus producing regions of the state were evaluated, Litoral Norte and Recôncavo Sul. Ten samples from the state of São Paulo, Brazil, were used for comparison. The following primers were used: ASSR20, OSSR9, OSSR17, CSSR4, CSSR12, and CSSR20, of which the last four allowed the identification of 22 polymorphic loci. The citrus populations of X. fastidiosa in the state of Bahia have high genetic diversity, based on SSR markers, with distinct gene pools and geographical grouping. In Litoral Norte, the populations of the isolate show higher genetic diversity than those in the Recôncavo Sul region of Bahia.